2018
DOI: 10.3892/or.2018.6948
|View full text |Cite
|
Sign up to set email alerts
|

miR‑498 inhibits the growth and metastasis of liver cancer by targeting ZEB2

Abstract: MicroRNAs (miRNAs) play critical roles in the growth, metastasis and therapeutic resistance of liver cancer. Accumulating evidence suggests that miR-498 is aberrantly expressed in several human malignancies. However, the role and underlying mechanism of miR-498 in liver cancer remain unclear. In the present study, we investigated the potential roles and clinical value of miR-498 in liver cancer. We found that the miR-498 expression level was significantly lower in liver cancer patient tissues than that in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
3
51
0
3
Order By: Relevance
“…One of the main functions of ZEB2 is to promote tumorigenesis and development by regulating EMT. Previous studies have confirmed that ZEB2 is related to infiltration and metastasis of multiple types of carcinomas, such as gastric malignancy, 36 liver malignant tumor 37 and non-small cell lung carcinoma. 38 In BC, Ang et al pointed out that the positive expression rates of ZEB2 mRNA and protein in ER-positive and ER-negative BC were different, but there was no significant statistical difference.…”
Section: Discussionmentioning
confidence: 80%
“…One of the main functions of ZEB2 is to promote tumorigenesis and development by regulating EMT. Previous studies have confirmed that ZEB2 is related to infiltration and metastasis of multiple types of carcinomas, such as gastric malignancy, 36 liver malignant tumor 37 and non-small cell lung carcinoma. 38 In BC, Ang et al pointed out that the positive expression rates of ZEB2 mRNA and protein in ER-positive and ER-negative BC were different, but there was no significant statistical difference.…”
Section: Discussionmentioning
confidence: 80%
“…miRNA-485-5p (miR-485-5p) strained EC tumorigenesis and could provide as a novel candidate for therapeutic applications in EC treatment [11]. MiR-498 has been verified to be one of the significant determinants of cell tumorigenicity in all kinds of tumors [12,13]. Zinc finger E-box-binding homeobox 2 (ZEB2) is structurally connected E-box binding homeobox transcription factors that induce epithelial mesenchymal transition (EMT) during development and disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…The miRNAs mediate the cell survival, proliferation, apoptosis, tumor growth, and metastasis by acting as a regulators of genes expression [8] . It has been widely reported that miR-498 were involved in the regulation of various cancers and were considered to be the prognostic biomarker and therapeutic target for prostate cancer [9] , triple negative breast cancer [10] , esophageal squamous cell carcinoma [11] , liver cancer [12] and non-small cell lung cancer [13] . A previous study has found the overexpression miR-498 inhibits gastric cancer cell proliferation, migration and invasion and the long non-coding RNA UFC1 promotes gastric cancer progression by regulating miR-498/Lin28b [14] .…”
Section: Introductionmentioning
confidence: 99%